Should magnesium be given to every migraineur? No - Párdutz Árpád (JOURNAL OF NEURAL TRANSMISSION, 2012)
Migraine is one of the most common neurological disorders that affects young people, causing a considerable degree of disability in the active population, with an enormous consequent socio-economic impact. Despite intensive research, the pathomechanism of migraine is not completely understood and its fully effective therapy remains to be achieved. A number of experimental studies have implicated the importance of magnesium ion in the pathophysiology of this condition. Magnesium has been also administered for both prophylactic and acute therapy in migraine, but the question of its efficacy has not been studied adequately. The data available suggest that magnesium has a potential role in the prophylaxis, but the results in acute therapy are far less convincing. With a good side effect profile, magnesium is a relatively safe drug with a possible beneficial effect in the prophylaxis of migraine headache, and it may have its niche in the treatment of migraine patients. However, the current medical evidence that has accumulated and the fact that there are far more effective treatment possibilities clearly indicate that this drug is definitely not to be used by every migraineur.